Revitalisasi Peran Penghulu dalam Meminimalisir Pernikahan Dini di Kota Palopo - Bahtiar, Bahtiar; Marwing, Anita; Kaddase, Muh. Thayyib (Al-Mizan (e-Journal), 2025)
This research aims to examine the revitalization of the role of the Penghulu (the marriage officiant) in minimizing early marriage in Palopo City. The research method used is qualitative with a descriptive approach. Data was obtained through in-depth interviews, observations and document studies related to the role of the headman and the efforts made to reduce the rate of early marriage. The research results show that the Penghulu has a very important role in carrying out religious duties, especially in registering marriages, as well as providing guidance and advice to the prospective bride and groom. Apart from that, the headman also plays an active role in efforts to prevent early marriage through various strategies, such as direct and online outreach, as well as collaboration with related agencies, such as the Population Control and Family Planning Service, the Health Service, and community organizations. By utilizing social media and building cross-sector collaboration, the Penghulu and the Palopo City government succeeded in strengthening preventive efforts to reduce the number of early marriages. The revitalization of the role of the Penghulu is carried out through increasing capacity through training and workshops, as well as implementing digitalization strategies for public education.